INFLUENCE of HIP EXTERNAL ROTATION on HIP ADDUCTOR and RECTUS FEMORIS MYOELECTRIC ACTIVITY DURING A DYNAMIC PARALLEL SQUAT - Pereira, Glauber Ribeiro; Leporace, Gustavo; Chagas, Daniel Das Virgens; Furtado, Luis F. L.; Praxedes, Jomilto [UNESP]; Batista, Luiz A. (Lippincott Williams & Wilkins, 2010)
Pereira, GR, Leporace, G, Chagas, DV, Furtado, LFL, Praxedes, J, and Batista, LA. Influence of hip external rotation on hip adductor and rectus femoris myoelectric activity during a dynamic parallel squat. J Strength Cond Res 24(10): 27492754, 2010-This study sought to compare the myoelectric activity of the hip adductors (HAs) and rectus femoris (RF) when the hip was in a neutral position or externally rotated by 30 degrees or 50 degrees (H0, H30, and H50, respectively) during a parallel squat. Ten healthy subjects performed 10 repetitions of squats in each of the 3 hip positions and the myoelectric activities of the HAs and RF were recorded. The signal was then divided into categories representing concentric (C) and eccentric (E) contractions in the following ranges of motion: 0-30 degrees (C1 and E1), 30-60 degrees (C2 and E2), and 60-90 degrees (C3 and E3) of knee flexion. From those signals, an root mean square (RMS) value for each range of motion in each hip position was obtained. All values were normalized to those obtained during maximum voluntary isometric contraction. We found that HAs showed a significant increase in myoelectric activity during C3 and E3 in the H30 and H50 positions, as compared with H0. Meanwhile, RF activity did not significantly differ between hip positions. Both muscles showed higher activation during 60-90 degrees (C3 and E3) of knee flexion, as compared with 0-30 degrees (C1 and E1) and 30-60 degrees (C2 and E2). The results suggest that if the aim is to increase HA activity despite the low percentage of muscle activation, squats should be performed with 30 degrees of external rotation and at least 90 degrees of knee flexion.
Keywords: squat; hip rotation; EMG; biomechanics; resistance training